Akibat Hukum Wanprestasi Dalam Perjanjian Sewa Menyewa Lahan Antara Pemilik Dengan Pihak Bumdes Di Kawasan Wisata Senggigi Tanjung Bias - M. Yazid Fathoni; Sahruddin Sahruddin; H. Zaenal Arifin Dilaga (Private Law, 2022)
The utilization of the coastal border area for business in Senteluk Village Batulayar District usually make a conflict, especially between the businessman and the people who claim to be land owners, in a lease agreement legal relationship. Based on this case, the study's purpose is to find out the status of the land or lease agreement object in the coastal border area. The research method in this research is normative-legal research. The result of this study showed that first, land or lease agreement objects in Tanjung Bias could be analyzed based on two perspectives. In the first perspective, If we analyze the legislation, the land is a coastal border, it is meant that the area should be possessed and managed by the state. In the second perspective, the coastal border is the private land owner and not the state owner because the owner has a certificate or authentic evidence to prove her land. The court decision showed that the land or lease agreement object at the coastline border area is the owner of the plaintiff or individual rights. If the party default so the lessee or the landowner has the right to null and void the lease agreement or they could make another legal action based on the legislation